PERBAIKAN KUALITAS LAYANAN PERBANKAN MELALUI METODE SIX SIGMA - Eka Dyah Setyaningsih (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2015)
In the face of 'the people AEC 2015 Start It should fix that kita Economy Remain stable . The efforts made hearts is the World Bank About quality services should perform Repairs - Repair Services hearts shown to customers hearts for support the transaction. The author took the research object is quality service Consisting Of Physical Evidence, reliability, power with a response, we are talking about the assurance, empathy through the use of six sigma method with 23 Questions posed. Six sigma method is done to solve problems with the application of DMAIC (Define, Measure, Analyze, Improve, Control). Through DMAIC Step by Step -masing so until found the root of the problem which affects the findings Must End Its indeed improved. Should the results be improved Namely findings - findings are documented and disseminated quality improvement, Practices - Best Practices The success hearts improve standardized process and used as a standard work guidelines quality services. Based on the findings of the study it can be stated that the root of the problem are obtained in order for the steps  that must achieved Keywords : Banking , quality service , using six sigma method